The epidemiology and burden of childhood rotavirus infection in a tertiary hospital in Sabah, Malaysia - Goh, C.T.; Cheah, P.K.; Soo, T.L.; Lee, Way Seah (Malaysian Medical Association, 2009)
We aimed to determine the epidemiology and burden of rotavirus (RV) gastroenteritis (GE) in children requiring hospital care in an urban setting in Sabah, Malaysia. A prospective study of all patients younger than 12 years of age admitted with acute GE to Queen Elizabeth Hospital, Sabah, over a six-month period (October 2005 to March 2006) was conducted. During the study period, a total of 167 children with acute GE who had stool samples examined for RV were studied. RV accounted for 16 of all diarrhoeal cases, and 1.7 of all admissions to the children's wards during the study period. There was no difference in severity of GE between RV and non-RV groups. RV infection is a common cause of childhood GE requiring hospital care in Sabah.